O Modelo de Sacerdote na Província de São Lourenço de Brindes, mudanças, permanências e reflexos no acompanhamento vocacional da crise do Vaticano II à 2008. - Santos, Rodrigo Carneiro dos (2009)
The present work, linked to the History, culture and citizenship line of research, of the Program of Master's degree in Applied social sciences of the State University of Ponta Grossa, has for objective to analyze the transformations happened in the Brazilian society and their interferences in the model of priest in the Ordem dos Frades Menores Capuchinhos of the Province of São Lourenço de Brindes, between Vaticano II and the year of 2008. For that, it characterizes aspects of the History of Brazil during the studied period, besides rescuing characteristics of the appearance of the franciscanism till its performance in the Brazilian society in XXI century and explores the experiences and existences of the exits of the Capuchinhos congregation and the influence exercised for the Franciscan identity in their daily pos-seminar.